2017
DOI: 10.1038/cddis.2017.328
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA CRNDE promotes colorectal cancer cell proliferation via epigenetically silencing DUSP5/CDKN1A expression

Abstract: Evidence indicates that long non-coding RNAs (lncRNAs) play a critical role in the regulation of tumor cellular processes, such as proliferation, apoptosis, and metastasis. LncRNA CRNDE (Colorectal Neoplasia Differentially Expressed) is located at human chromosome 16 and has been found overexpressed in a variety of cancers including colorectal cancer (CRC). In this paper, we report that lncRNA CRNDE expression was remarkably upregulated in CRC tissues and that lncRNA CRNDE overexpression was positively correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
131
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 146 publications
(135 citation statements)
references
References 38 publications
4
131
0
Order By: Relevance
“…In addition to their dysregulated expression and clinical associations, the involvement of lncRNAs in cancer initiation, progression, and prognosis has been eagerly studied . Examples include lncRNA MRCCAT1 (metastatic renal cell carcinoma‐associated transcript 1) expression being raised in metastatic foci with the ability to strengthen metastasis in clear cell renal cell carcinoma and the high expression of lncRNA CRNDE (colorectal neoplasia differentially expressed) associated with enlarged tumor size, advanced pathological stages, and reinforcing apoptotic and proliferative capacity in colorectal cancer . In the present study, we overexpressed and silenced lncRNA‐CTD‐2108O9.1 to examine its biological function in BC cells.…”
Section: Discussionmentioning
confidence: 91%
“…In addition to their dysregulated expression and clinical associations, the involvement of lncRNAs in cancer initiation, progression, and prognosis has been eagerly studied . Examples include lncRNA MRCCAT1 (metastatic renal cell carcinoma‐associated transcript 1) expression being raised in metastatic foci with the ability to strengthen metastasis in clear cell renal cell carcinoma and the high expression of lncRNA CRNDE (colorectal neoplasia differentially expressed) associated with enlarged tumor size, advanced pathological stages, and reinforcing apoptotic and proliferative capacity in colorectal cancer . In the present study, we overexpressed and silenced lncRNA‐CTD‐2108O9.1 to examine its biological function in BC cells.…”
Section: Discussionmentioning
confidence: 91%
“…A large number of studies have shown that EZH2 is closely related to tumorigenesis and development. For example, lncRNA CRNDE inhibits the expression of downstream target gene DUSP5/CDKN1A by binding EZH2 and promotes the proliferation of CRC cells . In addition, Linc00460 regulates proliferation of CRC cells by recruiting EZH2 and AGO2 to regulate the downstream target gene KLF2/CUL4A .…”
Section: Introductionmentioning
confidence: 99%
“…Antisense ncRNA in the INK4 locus (ANRIL) can recruit SUZ12 to repress the expression of P15 INK4B locus [22]. LncRNA CRNDE interacts with EZH2 and repress DUSP5/CDKN1A expression in CRC [29]. According to our previous studies, lncRNA HOXA-AS2 promotes CRC progression partially via silencing P21 and Kruppel-like factor 2 (KLF2) expression through histone 3 lysine 27 trimethylation (H3K27me3) mediated by EZH2 [30].…”
Section: Introductionmentioning
confidence: 99%